The Periodic Table of Food Initiative (PTFI): An initial list of the world’s food diversity for compositional investigation - Jarvis, Andy; Gallo-Franco, Jenny; Portilla, Julian; German, Bruce; Debouck, Daniel; Rajasekharan, Maya; Colin, Khoury K.; Herforth, Anna; Ahmed, Selena; Tohme, Joe; Arnaud, Elizabeth; Christopher, Golden D.; et al. (2024)
Here we report a list of diverse and culturally relevant foods that justify compositional cataloging as part of the Periodic Table of Food Initiative (PTFI). The PTFI is a participatory project aimed at addressing food composition information gaps worldwide through a standardized, accessible, and enabling platform based on state-of-the-art nutritional analytical technology. Through data analytics and engagement with experts across the globe, here we identify 1650 important foods for biochemical compositional analysis.